2021
DOI: 10.18231/j.jchm.2021.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microalbumin, cystatin c, creatinine and uric acid levels in HIV patients in Nnamdi Azikiwe University Teaching Hospital, Nnewi

Abstract: This study evaluated the microalbumin, cystatin C, creatinine and uric acid levels in HIV patients in Nnamdi Azikiwe University Teaching Hospital, Nnewi (NAUTH). A total of one hundred (100) male and female HIV positive and control participants who were aged between 18 and 60 years attending the voluntary counseling and testing unit (VCT) and antiretroviral therapy unit (ART) of NAUTH were randomly recruited for the study and grouped thus: Group A (HIV positive symptomatic participants on long term ART (HPSPLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Accordingly, patients taking ART for more than 24 months were two times more likely to have hyperuricemia. This is similar to studies done in China and Nigeria ( 23 , 65 ). Patients treated with a DTG-based regimen had a two-fold higher risk of developing hyperuricemia, which was in agreement with a study finding from China ( 59 ), which showed the number of patients with hyperuricemia increased with DTG-containing ART.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, patients taking ART for more than 24 months were two times more likely to have hyperuricemia. This is similar to studies done in China and Nigeria ( 23 , 65 ). Patients treated with a DTG-based regimen had a two-fold higher risk of developing hyperuricemia, which was in agreement with a study finding from China ( 59 ), which showed the number of patients with hyperuricemia increased with DTG-containing ART.…”
Section: Discussionsupporting
confidence: 91%
“…An increased risk of having hyperuricemia was seen among treatment-naive compared to treatment experienced people living with HIV ( 21 , 22 ). It is observed that hyperuricemia was also detected in HIV patients taking HAART ( 23 , 24 ). Accordingly, a study from Italy reported that 25.2% of people living with HIV on HAART developed elevated serum uric acid levels ( 12 ).…”
Section: Introductionmentioning
confidence: 99%